The Color Change of Jabon Wood Stained by Bark Extract of Samak Wood (Syzygium inophyllum) - Muflihati Muflihati; Deded S Nawawi; Istie S Rahayu; Wasrin Syafii (Masyarakat Peneliti Kayu Indonesia, 2014)
The water soluble extract of samak (Syzygium inophyllum) bark was applied as natural dye for jabon wood (Anthocephalus cadamba). Ten percent of the extract concentration was used for staining of jabon wood by soaking methods for 74 h at room temperature, and for 3 h at 70 oC, respectively. The stained jabon wood performances were evaluated as the color change and stability by hot water leaching test. The stained and leached woods were assessed by determination of color changes using CIELab method and FTIR analysis. Based on the CIELab analysis, the brightness (L* value) of stained jabon wood decreased, and tend to more reddish (a* value increased) and yellowish (b* value slightly increased) compared to these of unstained wood, as the results, the color of jabon wood changed from light grey to reddish orange after staining with samak bark extract. The leaching test of stained wood to hot water changed the color from reddish orange to dull orange. FTIR analysis indicated that part of the extract stained jabon wood was quite stable to hot water treatment.Key words : bark extract, jabon wood, natural dye, samak wood, Syzygium inophyllum